IMPLEMENTASI KEBIJAKAN PROGRAM BANTUAN LANGSUNG TUNAI-DANA DESA BAGI MASYARAKAT MISKIN TERDAMPAK COVID-19 DI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Juniyanti Tuarita; Nensy Lusida (Jurnal Administrasi Terapan, 2023)
Indonesia was hit by a major disaster, namely the Covid-19 pandemic, due to this Covid-19 pandemic not only having a social impact on Indonesia but also having a negative impact on the Indonesian economic sector, this has increased the number of poor people in Indonesia. The government's efforts to prevent an increase in the number of poor people in Indonesia, the Indonesian government launched a number of social assistance, one of which was direct cash assistance from village funds (BLT-DD). during the Covid-19 pandemic, and one of them was the poor community of Salahutu District who also received this program. So this study was conducted to determine the implementation of the Cash Direct Assistance program policy for the poor affected by Covid-19 in Salahutu District, Central Maluku Regency.The research was carried out for 1 month from September 7 to October 7, 2022 in 6 countries in Salahutu sub-district namely Liang, Suli, Tulehu, Tengah, Tial and Waai. There are 9 informants or research subjects. This study uses a descriptive qualitative method design. Data collection techniques used include interviews, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions.This study uses the theory of policy implementation from Van Meter and Van Horn which has 6 policy implementation variables and from the results of this study that the BLT-DD program is still not running well because there is maladministration in its implementation.Keywords: Policy Implementation, Covid-19 Pandemic, BLT-DD Program